Papaya carotenoids increased in Oxisols soils - Sangsoy, Kamonwan; Mongkolporn, Orarat; Imsabai, Wachiraya; Luengwilai, Kietsuda (Agriculture and Natural Resources, 2017)
The papaya fruit is healthy for humans as it contains high levels of antioxidants and provitamin A due to high lycopene and β-carotenes contents, respectively. The carotenoids were determined from papayas grown in three different locations-Kamphaeng Saen (KS), Sisaket (SK), and Tha Mai -(TM)-and also the study investigated whether the Oxisols soil was capable of increasing the carotenoids content in the papaya fruit. The lycopene, β-carotene and β-cryptoxanthin contents were determined from four different ripening stages (mature green to fully ripe). Concomitantly, the transcript levels of five genes involved in carotenoids biosynthesis-phytoene desaturase (PDS), carotene desaturase (ZDS), lycopene-β-cyclase (LCY-B1 and LCY-B2), and β-carotene hydroxylase (B-CHX)-were investigated. Papayas grown at TM had the highest lycopene, which was supported by the high expression levels of PDS, ZDS and BCHX and the lower expression levels of the two LCY-B genes; however the locations did not affect the fruit quality. The ‘Plak Mai Lai’ papaya was further investigated by being grown in one location but on two different soil types (Oxisols and Ultisols), to compare their carotenoids contents. Higher carotenoid contents were detected in the papaya grown in the Oxisols.